Trellis orthogonal reconstruction algorithm based on orthogonal space-time block code for wireless communication system in high-speed railway - Wan-tuan LUO; Xu-ming FANG; Meng CHENG (Tongxin xuebao)
A detailed analysis of open-loop (OL) and closed-loop (CL) multiple input multiple output (MIMO) scheme based on orthogonal space-time block code (OSTBC), and lays emphasis on how the velocity influences the OSTBC in high-speed railway scenario is provided. When the train moves at a fantastic speed, the fast time-varying channel destroys the orthogonality of OSTBC reducing the diversity gain which would severely degrade the bit error rate (BER) perform-ance. The trellis orthogonal reconstruction algorithm (TORA), in which the intra-code orthogonality is reconstructed through givens transformation and the transmit beamforming direction can be changed as well is proposed. In high-speed railway scenario, this proposal obtains not only the array gain by transmit beamforming, but also the same diversity gain as the train is motionless. The simulation shows that the TORA improves BER performance of MIMO schemes based on OSTBC for mobile communication system in high-speed railway.